Comparison of Dynamics of Udder Skin Microbiota From Grazing Yak and Cattle During the Perinatal Period on the Qinghai–Tibetan Plateau - Zhang, Jianbo; Ahmad, Anum Ali; Jia, Yan; Dingkao, Renqing; Du, Mei; Liang, Zeyi; Zheng, Juanshan; Bature, Ibrahim; Yan, Ping; Salekdeh, Ghasem Hosseini; Ding, Xuezhi (Frontiers in Veterinary Science, 2022)
The perinatal period has an important impact on the health of ruminants, and the imbalance ud-der skin microbiota might be an important inducement of bovine mastitis. However, it is not clear how the perinatal period affects the microbial structure and stability of udder skin of yak and cattle. Here, we used 16S rRNA gene high-throughput sequencing to analyze udder skin microbiota of yak and cattle during the perinatal period. We found that the diversity and rich-ness of microbiota of bovine udder skin during 1-2 weeks postpartum were significantly lower than those in the 1-2 weeks prenatal and 1 month postpartum (Wilcoxon, p < 0.05). Besides, we found 2,533 OTU-sharing in the udder skin microbiota of yak and cattle during the perinatal period, among which the core microbiota at the genera level was mainly composed of Staphy-lococcus, Moraxella, and Acinetobacter. However, the genus Acinetobacter was significantly abundant in udder skin of cattle during 1-2 weeks postpartum. The NMDS and LEfSe results showed that the perinatal period had more effects on the composition and stability of microbial community in udder skin of cattle compared to yak, especially in 1-2 weeks postpartum. In ad-dition, the average content of total whey proteins and Immunoglobulin G of whey protein in yak colostrum were significantly higher compared to cattle (p < 0.05). In conclusion, the struc-ture of udder skin microbiota of yak during the perinatal period is more stable than that of cat-tle in the same habitat, and 1-2 weeks postpartum may be a potential window period to prevent cattle mastitis.